Academic promotion in Malaysian public universities: a critical look at issues and challenges - Azman, Norzaini; Che Omar, Ibrahim; Md. Yunus, Aida Suraya; Md Zain, Ahmad Nurulazam (Routledge, 2016)
The expansion and transformation of Malaysian universities have generated major changes in the nature of academic employment and the structure of academic promotion in higher education institutions. These changes have considerable implications, in particular for the policy and practice of academic promotion in the public universities. We argue that despite sharing one common grade and salary system, distinct and significant differences exist in the academic promotion systems of the public universities. Drawing on one recent study on the academic promotion process in Malaysian public universities to contextualise our discussion, this paper highlights the complexity in the promotion process in these institutions. It also discusses and articulates the attendant issues and challenging aspects of the academic promotion process. We argue that the interrelated issues and challenges, and certain academic practices and habits stemming from the pressure to gain a promotion are pervasive, and that they affect the academic value system and work culture. We conclude by asserting the importance of applying a consistent standard for promotion within a single salary system and that the academic promotion system in the public universities should ultimately affirm and communicate core academic values, and also aim at obtaining evidence of excellent accomplishments.